Clinical outcome and toxicity of radiotherapy for inferior vena cava tumor thrombus in HCC patients: A retrospective study. Issue 25 (25th June 2021) - Lee, So Jung; Jang, Hong Seok; Choi, Yoo Kyung
Abstract : Abstract: Hepatocellular carcinoma (HCC) involving the inferior vena cava rarely occurs, but its prognosis is extremely poor, with no established treatment to date. This study aimed to analyze the clinical outcome and toxicity of radiotherapy (RT) targeting inferior vena cava tumor thrombus (IVCTT) in HCC patients. From November 2011 to July 2020, medical record of 19 HCC patients who were treated with RT for IVCTT was retrospectively reviewed. RT was delivered using 3-dimensional conformal radiation therapy, intensity-modulated radiation therapy, and stereotactic body radiation therapy. The median radiation dose was 50 Gy (range, 45–55.8 Gy) for intensity-modulated radiation therapy and three-dimensional conformal radiotherapy. Stereotactic body radiation therapy was performed in 5 patients, for a total of 32 Gy in 4 fractions. The median follow-up duration was 8.1 months (range, 3.3–26.5 months). The median overall survival was 9.4 months (range, 3.7–26.5 months), and the 1-year overall survival rate was 37.1%. Eight of 19 patients (42.1%) had extrahepatic metastasis at the start of RT. Six of 11 patients (54.5%) who did not have extrahepatic metastasis at the start of RT showed extrahepatic metastasis after RT. The major cause of death was progression of extrahepatic metastasis (11 patients, 57.9%). The overall response rate of IVCTT for RT was 84.2%, and the local control rate at the time of the last follow-up was 89.4%. After RT, the most common first progression site was the lungs (9 patients, 47.4%). Most toxicities were grade 1 to 2 gastrointestinal (26.3%) and liver enzyme elevation (68.4%). Three patients occurred pulmonary embolism after RT later than 5 months after. RT is a feasible and safe local therapy for IVCTT, with favorable tumor control and acceptable toxicity. Extrahepatic metastasis is the major progression pattern and a leading cause of death in patients treated with RT. The combination of effective systemic therapy with RT may have to be considered.